Frank and the skunk : with four phonics stories - Rae, Elspeth, 1973-; Rae, Rowena (Rae, Elspeth, 1973- Meg and Greg, 2020)
"This partially illustrated workbook, meant to be read by an advanced reader with a beginner reader or struggling reader, combines stories and exercises that focus on phonics."--